The Communication System of Surabaya Main Waste Bank (BSIS): A Study on Environmental Education and Community Empowerment through Participatory Waste Management - A'zdom, Muhammad Khofidul; Asilah, Amirah Salwa (Professorline, 2025)
The Surabaya Main Waste Bank (BSIS) represents an innovative approach to urban waste management by integrating environmental, social, and educational dimensions. This study aims to explore the communication system of BSIS and its role in supporting environmental education and community empowerment, particularly in the context of its integration with educational institutions. Employing a descriptive qualitative approach through a case study method, data were collected via observation, interviews, and document analysis. The findings reveal that BSIS functions not only as a waste management center but also as an environmentally oriented community learning space. Its structured and educational communication strategies enable BSIS to serve as a real-life learning laboratory for schools, particularly in supporting Adiwiyata programs and contextual, cross-curricular learning. Nevertheless, the study identifies key challenges, including the limited formal integration with educational institutions and the lack of teacher training related to community-based environmental education.To address these challenges, the study highlights the need for curriculum integration and community-based teacher training programs to strengthen the synergy between environmental management and sustainable education.